The Feasibility of Student Worksheet based on Collaborative Creativity to Improve Students Creative Thinking Skill - Suliyanah Suliyanah; Romafika Oktafina; Utama Alan Deta (Program Studi Pendidikan Fisika FKIP Universitas Lambung Mangkurat, 2020)
This study aims to describe the feasibility of the student worksheet based on collaborative creativity to improve creative thinking skills on static fluid material in terms of validity, practicality, and effectiveness. This type of research is a type of development research by the ADDIE model with one group pre-test post-test experimental design method. The trial subjects were 107 students from class XI-MIPA 1, XI-MIPA 3, and XI-MIPA 4 in SMAN 1 Sumberrejo. The instruments used were validation instruments, observation instruments for the practicalities of the student worksheet, test instruments, and questionnaires to measure the student worksheet's effectiveness. The results showed that the validity of the student worksheet was included in the very valid category. In terms of the implementation of learning and student activities, the student worksheet practicality criteria are in the excellent category. The student worksheet's effectiveness criteria, based on test results, are in the medium category, and students' responses are very effective. Thus, the student worksheet that has been developed can improve creative thinking skills in learning the physics of static fluid material.